DESIGNING MaPicA: POWERPOINT- BASED INSTRUCTIONAL MATERIAL TO INVOLVE REFUGEE STUDENTS TO SPEAK ACTIVELY - HANDAYANI, MAGPIKA; Salam, Urai; ., Sudarsono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: This study uses the research and development approach. The purpose of this research is to develop a Powerpoint based-instructional material for teaching speaking to the refugees at Detention Center Pontianak in getting them involved actively in speaking class by combining material, picture and animated pictures (MaPicA). In developing this product, need analysis is done in order to find the need of the students for speaking class. Based on the need analysis, a product is designed, developed and implemented to the class. The product is PowerPoint-based instructional material which consists of 91 slides, 1 slide for the cover of the product that explains about what the product is, 1 slide is to guide the user of the product, 1 slide is to display the theme of discussion and divided into 2, on the right is for theme and on the left is for pictures as well as animated pictures, 1 slide is to display audio and 1 slide is for each grammar and exercise while there are 86 slides are used for the content of the material.  The result applied to the large group shows a consistency between the first and the second try out on students’ performance. The result of second try out shows the improvement in the number of students involved in the class discussion.  Besides, this product is able to establish a clear link between the topic being discussed and its uses in the real world, moreover, the students are able to use it for their communication.  Keywords: Instructional Material, MaPicA, Speaking Actively.Abstrak: Penelitian ini menggunakan pendekatan penelitian dan pengembangan. Tujuan dari penelitian ini adalah untuk mengembangkan materi pembelajaran berbasis powerpoint untuk mengajar kemampuan berbicara kepada pengungsi pada rumah detensi imigrasi Pontianak sehingga mereka terlibat aktif dalam berbicara di kelas dengan menggabungkan materi, gambar dan gambar animasi (MaPicA). Dalam mengembangkan produk ini,analisis kebutuhan dilakukan untuk menemukan kebutuhan para siswa dalam melatih kemampuan berbicara mereka. Berdasarkan analisis kebutuhan tersebut produk dirancang, dikembangkan dan diimplementasikan di kelas. Produk ini adalah materi pembelajaran berbasis powerpoint yang terdiri dari 91 slide, 1 slide untuk sampul produk yang menjelaskan tentang produk ini, 1 slide adalah arahan dalam menggunakan produk ini, 1 slide untuk menampilkan tema diskusi dan dibagi menjadi 2, di sebelah kanan untuk tema dan di sebelah kiri adalah untuk gambar serta gambar animasi, 1 slide untuk tampilan audio dan 1 slide untuk setiap tata bahasa dan latihan, sementara ada 86 slide yang digunakan untuk isi materi. Dari hasil yang diuji coba pada kelompok besar, siswa menunjukkan konsistensi pada uji coba pertama dan kedua. Hasil uji coba kedua menunjukkan peningkatan jumlah siswa yang terlibat dalam diskusi di kelas. Selain itu, produk ini mampu membangun hubungan yang jelas antara topik yang sedang dibahas dan penggunaannya pada situasi yang sebenarnya, lebih dari pada itu, siswa dapat menggunakannya dalam komunikasi.  Keywords: Materi Pembelajaran, MaPicA, Berbicara Aktif.